Motivational elements of digital instructional games: A study of young L2 learners' game designs. (November 2017) - Butler, Yuko Goto
This article focuses on the design of digital instructional game (DIG) tasks for young second language (L2) learners. The aim of the study is to identify motivational task elements based on what children respond to positively in games and incorporate into their own L2 vocabulary learning game designs. Eighty-two sixth-grade students (ages 11–12 years) in Japan were first asked to identify game elements by examining existing games and then to design games incorporating DIG tasks of their own and peer-evaluate them. Building on previous work (Butler, 2015), the study uses a mixed-methods approach to examine how both task-intrinsic characteristics and implementation conditions were realized in innovative and engaging DIG tasks by children. Although the study focuses on young learners, the findings might be applied to any type of task, including both digital and physical tasks for adults as well as for children. The article concludes with suggestions for how to design instructional materials which allow individualized learning and encourage autonomy in order to cater to the genuine interests of learners and to invoke intrinsic motivation for learning.